Trauma, fragmentation and narrative: Sandor Ferenczi's relevance for psychoanalytical perspectives on our response to climate change and environmental destruction. (28th June 2019) - Bellamy, Alan
Abstract: Psychoanalytical perspectives on our responses to climate change and environmental destruction may be said to have begun with Harold Searles in 1972 and have gathered pace in recent years. All these explorations have in common a reliance on a set of conceptual ideas that were initially developed by Sandor Ferenczi, although he is rarely credited. Fully acknowledging of the extent of environmental destruction and climate change is seen as traumatic in these writings, and therefore, concepts that have been developed in working with patients traumatized by abuse have been found essential in trying to understand and describe our responses. This paper will show how Ferenczi's thinking about trauma and about the therapeutic relationship has influenced recent suggestions as to how a psychoanalytical perspective may help us to explore attitudes and beliefs and help others to fully acknowledge the seriousness of climate change and so change damaging behaviors.